A new quadrivalent meningococcal tetanus toxoid conjugate vaccine: Menquadfi® (MENACWY-TT) - Ener Cagri Dinleyici; Ergin Ciftci; Ayper Somer; Dilek Yilmaz; Hasan Tezer (Human Vaccines & Immunotherapeutics)
Neisseria meningitidis (Nm) remains a major global health concern, causing invasive meningococcal disease (IMD) with significant morbidity and mortality. Despite vaccination efforts, Nm serogroup prevalence and antibiotic resistance continue to evolve, necessitating ongoing surveillance and novel immunization strategies. This review aims to assess the role of MenACWY-TT, a quadrivalent meningococcal conjugate vaccine, in IMD prevention by evaluating its immunogenicity, safety, and real-world effectiveness. The objectives include analyzing its advantages over existing vaccines, identifying gaps in long-term immunity data, and assessing its potential integration into National Immunization Programs (NIPs). MenACWY-TT has demonstrated strong immunogenicity, a favorable safety profile, and ease of administration with its liquid, non-adjuvanted formulation. Real-world studies show high vaccine effectiveness and herd protection benefits. However, further research is needed to evaluate long-term immunity and efficacy in high-risk populations.